Psoriasis: from Pathogenesis to Targeted Therapies - Conrad, Curdin; Gilliet, Michel (Clinical reviews in allergy & immunology, 2018)
Over the last decade, the management of psoriasis has witnessed a paradigm shift. Thanks to the increasing knowledge about the pathogenesis of psoriasis, targeted treatments with monoclonal antibodies have been developed. These antibodies, which target the pathogenic TNF/IL-23/IL-17-pathway, were shown to be safe and efficacious in the management of most patients with moderate to severe chronic plaque psoriasis. Recently, molecular and genetic studies in pustular and erythrodermic psoriasis have identified additional inflammatory pathways, providing evidence that psoriasis is a heterogeneous disease and highlighting the requirement for personalized disease characterization for treatment optimization. In this article, we will review these advances and provide an update on the currently available treatment arsenal. We discuss the efficacy and safety profile of these individual therapeutic agents and describe their use in special indications. We will also describe the current understanding of psoriasis as a systemic disease associated with multiple comorbidities and illustrate its impact in the management of psoriatic patients. Finally, we discuss ongoing therapeutic developments as well as unmet needs and future perspectives in the field of psoriasis.